A Systematic Literature Review: Problem-Solving Skills in Physics Teaching - Nisa, Khairun; Putri, Santri Adi; Kuswanto, Heru (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Empowerment of problem-solving skills is one of the many goals 21st-century education intends to achieve. This research employs content analysis on several articles published in journals between January 2017 and December 2022, primarily focusing on problem-solving skills in physics teaching. This study aims to identify annual trends in research on problem-solving skills in physics teaching, identify the most frequently researched physics materials related to these skills, and identify the most frequently used grade students as research subjects for these skills. This study uses content analysis guidelines as a research instrument. In this study's content analysis, there are four main aspects reviewed. These aspects include (1) the number of publications per year, (2) the type of research, (3) the research subjects, and (4) the material selected for research. The results of this study indicate that in 2020 there will be a higher increase compared to previous years. The most widely used research subjects. The topic most often used as research material was the topic of physics in general. Quantitative research and research and development (R&D) were the most commonly used types of research. The study's findings have led to the proposal of several recommendations for future research that prioritizes problem-solving skills. Some of these recommendations include increasing the diversity of types of research and reviewing the data analysis techniques used.